Reformulating The Concept of Maslahah: From A Textual Confinement Towards A Logic Determination - Iffatin Nur; Muhammad Ngizzul Muttaqin (Justicia Islamica, 2020)
Up to this contemporary era, the concept of maslahah developed by several leading Muslim scholars seems to be rather theocentric in a way that it is transfixed on the maslahah considerations contained in the texts (naás). This means that the concept of maslahah has so far been shadowed in the textual confinement so that the resulting maslahah becomes an old-fashioned, stagnant, and less-able concept for responding to the times’ challenges. This study aims to open up discourses and opportunities for the development and reformulation of maslahah in the current contemporary era. This qualitative study is library research. The data used were obtained from book literature, journals, and other writings related to maslahah and were analyzed using a content analysis method. The discussion was done by describing the historical data of previous thoughts on maslahah from textual confinement to logic determination, which was then formulated with the reality of today's modern era life. The results of this study indicate that: 1) from its historical aspect, the reformulation of maslahah is one which has so far only been assessed in the perspective of Shari' (the Law Maker). Hence, it is necessary to reformulate it in the perspective of mujtahid by referring to maslahah associated with the issues’ reality context, 2) there is a need to incorporate the concept of ethics and humanity into the structure of maslahah, and 3) there present a necessity to formulate a collective-based ijtihad in probing of maslahah to create a scientific maslahah-based ijtihad methodology.